2015
DOI: 10.1037/pag0000026
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular function associated with fluid, not crystallized, abilities in older adults: A transcranial Doppler study.

Abstract: The brain is dependent on the cerebrovascular system, particularly microvasculature, for a consistent blood supply; however, age-related changes in this system affect neuronal and therefore cognitive function. Structural vascular markers and vascular disease appear to preferentially affect fluid cognitive abilities, sparing crystallized abilities. We sought to investigate the relationships between cerebrovascular function and cognitive domains. Fifty individuals between 60 and 75 years of age (31 women, 19 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…When assessing global cognitive function, the MoCA may be more useful than the MMSE for detecting cognitive impairment particularly in early stages of VCI [42]. Previous research has suggested that fluid abilities (e.g., information processing speed) may be more vulnerable to cerebrovascular dysfunction than crystallised abilities, at least at non-severe impairment stages [7,43]. Therefore, VCI-ND prevalence rates may be higher if the definition of VCI-ND includes impairment of fluid abilities.…”
Section: Discussionmentioning
confidence: 99%
“…When assessing global cognitive function, the MoCA may be more useful than the MMSE for detecting cognitive impairment particularly in early stages of VCI [42]. Previous research has suggested that fluid abilities (e.g., information processing speed) may be more vulnerable to cerebrovascular dysfunction than crystallised abilities, at least at non-severe impairment stages [7,43]. Therefore, VCI-ND prevalence rates may be higher if the definition of VCI-ND includes impairment of fluid abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the paradigms are the same and the current sample speaks English rather than German in the earlier work, the major difference between the populations is the age: between 17 and 50 in Knecht et al,average of 26; versus between 60 and 85, average of 69 in the current study. This may be the critical factor as language lateralisation is reported to reduce with aging (Keage et al, 2015;Matteis et al, 1998). The is consistent with increased rates of non- The work adds to the methods available for assessing lateralisation using fTCD in children, including Picture Naming (Haag et al, 2010;Lohmann et al, 2005), Story Listening (Stroobant et al, 2011), and Animation Description (Bishop et al, 2009 We employed two novel approaches to data exploration and retention using DOPOSCCI (Badcock, Holt, et al, 2012).…”
Section: What Box Language Lateralisation 21mentioning
confidence: 61%
“…Blood flow velocity was measured using a Doppler ultrasonography device (Doppler-Box™, DWL Elektronische Systeme, Singen, Germany) with a Diamon® headset or elastic headbands to hold 2-MHz transducer probes over the left and right temporal skull windows to insonate the middle cerebral arteries. Seated participants viewed the Psychtoolbox (Brainard, 1997;Pelli, 1997 Keage et al, 2015;Kohler et al, 2015).…”
Section: Functional Transcranial Doppler Ultrasonographymentioning
confidence: 99%
See 2 more Smart Citations